2003
DOI: 10.1128/aac.47.2.554-558.2003
|View full text |Cite
|
Sign up to set email alerts
|

Improved Pharmacokinetics and Reduced Antibody Reactivity of Lysostaphin Conjugated to Polyethylene Glycol

Abstract: Lysostaphin is a 27-kDa endopeptidase that enzymatically disrupts the cell wall of Staphylococcus aureus and is a promising candidate for treating S. aureus blood-borne infections. It would be extremely useful to define conditions that would both increase lysostaphin's in vivo half-life to allow for more effective tissue distribution and reduce its immunogenicity. Conjugation of polyethylene glycol (PEG) to lysostaphin (PEGylation) was investigated as a means to accomplish these goals. Rather than using linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
83
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 12 publications
3
83
0
Order By: Relevance
“…PEG moieties are inert, long-chain amphiphilic molecules produced by linking repeating units of ethylene oxide (33). PEGylation can decrease clearance, retain biologic activity, obtain a stable linkage, and enhance water solubility without significantly altering bioavailability (34). Moreover, PEG spacers are nontoxic and unreactive.…”
Section: Discussionmentioning
confidence: 99%
“…PEG moieties are inert, long-chain amphiphilic molecules produced by linking repeating units of ethylene oxide (33). PEGylation can decrease clearance, retain biologic activity, obtain a stable linkage, and enhance water solubility without significantly altering bioavailability (34). Moreover, PEG spacers are nontoxic and unreactive.…”
Section: Discussionmentioning
confidence: 99%
“…However, the 40-mg/kg dose resulted in peak levels of only 0.02 g/ml. The lysostaphin pharmacokinetics for adults appears different than that for neonates (26).…”
mentioning
confidence: 85%
“…Pups remained with their dams throughout the experiment. The Baylor College of Medicine Institutional Animal Use Committee approved the research.Three-day-old pups received 1 mg/kg of body weight/dose of lysostaphin at 1, 6, 24, and 30 h. Blood was obtained by cardiac puncture at 1,2,3,7,8,23,25,26,27, 31, 32, 72, and 96 h after the first dose. Three pups' blood was pooled for each data point, and each time point had two data points.…”
mentioning
confidence: 99%
“…Protein PEGylation, the covalent attachment of PEG chains to protein, is an effective method to reduce or overcome these problems (46,47). It has been shown that PEGylation of lysostaphin, conjugating PEG to the ε-amino groups of lysine residues, improves in vivo half-life and reduces immunogenicity, while bacteriolytic activity of PEGylated lysostaphin is diminished (48). Nonspecific reaction of PEG with lysostaphin at different sites produces a number of isomers, most of which have decreased binding affinity to the big network of cell wall peptidoglycan (see Fig.…”
Section: Discussionmentioning
confidence: 99%